Mucosal SARS-CoV-2 S1 adenovirus-based vaccine elicits robust systemic and mucosal immunity and protects against disease in animals - Najwa D. Aljehani; Levi Tamming; Muhammad Yasir Khan; Rwaa H. Abdulal; Mohamed A. Alfaleh; Aishah Ghazwani; Asalah Helal; Reem M. Alsulaiman; Mohammad A. Sanki; Khalid Alluhaybi; Farah Ayman Sukareh; Rahaf H. Alharbi; et al. (mBio)
ABSTRACT The COVID-19 pandemic has emphasized the importance and need for accessible safe, effective, and versatile vaccine platforms. While approved SARS-CoV-2 vaccines have been instrumental in saving lives and reducing healthcare and economic burdens, the induction of mucosal immunity remains an unmet need. Here, we engineered and evaluated a non-replicating adenovirus 5 (rAd5)-based vaccine expressing the SARS-CoV-2 S1 subunit (rAd5-SARS2-S1). We assessed the immunogenicity, durability, and protective efficacy of intramuscular (IM) and intranasal (IN) administration of rAd5-SARS2-S1 in mice and Syrian hamsters. Two IM or IN doses of rAd5-SARS2-S1 elicited robust and sustained Th1-skewed S1-specific serum IgG, neutralizing antibodies (nAbs) against several SARS-CoV-2 variants and systemic antigen-specific memory T cell responses in mice. Additionally, IN vaccination induced potent and long-lasting mucosal S1-specific IgG, IgA, and nAbs and pulmonary memory T cells. Importantly, while IM vaccine significantly ameliorated disease severity in hamsters by reducing viral burden, lung pathology, and, to some extent, weight loss, IN immunization significantly reduced viral replication and provided superior protection against disease and weight loss. Together, our study demonstrates that the rAd5-SARS2-S1 vaccine is immunogenic in both mice and hamsters when administered intramuscularly or intranasally, with IN administration providing better protection. These findings suggest that IN delivery of rAd5-SARS2-S1 could be a promising approach for inducing mucosal and systemic immunity, offering enhanced protection against SARS-CoV-2 and emerging variants.IMPORTANCEThis publication presents an assessment of the immune response and effectiveness of a vaccine containing genetically modified non-replicating recombinant that expresses the S1 subunit protein of SARS-CoV-2. We conducted a comparative analysis of the immune response potency, durability, and protective effectiveness of this vaccine using intramuscular (IM) and intranasal (IN) inoculation in mice and Syrian hamsters. Our findings indicate that both vaccinations were effective in stimulating strong and long-lasting immune responses, both locally and across the body, when administered through either IM or IN methods. Crucially, our study demonstrated that the IN vaccination outperformed the IM vaccine by effectively and significantly suppressing the multiplication of the virus in the lungs and nasal turbinates. Additionally, the IN vaccine provided protection against disease-related weight loss and lung damage in the animals. This work showcases the potential of intranasal administration as a viable method to stimulate both mucosal and systemic immunity. This technique provides improved defense against SARS-CoV-2 and maybe additional variations.